Cag-Cag Folk Games as Media to Strengthening Mutual Cooperation Character of Elementary School Students - Dewi, Komang Ayu Tantri Sastra; Agung, Anak Agung Gede; Abadi, Ida Bagus Gede Surya (Universitas Pendidikan Ganesha, 2023)
Individualism during group learning is a problem to be solved as it harms the mutual cooperation character of elementary school students. Therefore, this research aimed to analyze the effect of the Cag-cag folk game on strengthening the character of mutual cooperation in elementary school students. This research was a quasi-experimental study with a non-equivalent control group design. The population of this study was 681 students, and samples were selected using the cluster technique of random sampling. The observation was used as the data collection method. The data analysis involved descriptive and inferential statistical analyses and hypothesis testing using a polled variance t-test. The results showed that the calculated T value was 4.40, which was greater than the T table at the 5% significance level of 1.67, so it can be stated that there was a significant difference in students treated using the Cag-cag folk game. Based on the findings, it can be concluded that there was an influence exerted by the Cag-cag folk game on strengthening the mutual cooperation character of elementary school students.